Strategi Pengembangan Produk Unggulan Industri Kecil Bonggolan Kecamatan Sidayu Kabupaten Gresik - Muhammad Akbar Perdana; Alviolita Tri Amanda; Muhammad Yasin (Journal of Creative Student Research, 2023)
Bonggolan Small Industry is one of the leading products of Sidayu District, Gresik Regency which still requires further product development. The purpose of this study is to determine the Leading Product Development Strategy of Small Industry Bonggolan Sidayu District, Gresik Regency to increase its competitiveness so that it is known by the wider community. This study used descriptive analysis method through the results of Observation and Interview. The data analysis used is a SWOT analysis carried out to analyze internal and external factors of entrepreneurs in industrial estates. The results of this study show that there are 4 strength factors, 4 weakness factors, 5 opportunity factors and 4 threat factors so that 8 strategies can be formulated in developing superior products of the Bonggolan Small Industry, Sidayu District, Gresik Regency so that it can compete with other products and be known by the wider community.